2020
DOI: 10.1101/2020.03.02.974139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel bat coronavirus reveals natural insertions at the S1/S2 cleavage site of the Spike protein and a possible recombinant origin of HCoV-19

Abstract: SummaryThe unprecedented epidemic of pneumonia caused by a novel coronavirus, HCoV-19, in China and beyond has caused public health concern at a global scale. Although bats are regarded as the most likely natural hosts for HCoV-191,2, the origins of the virus remain unclear. Here, we report a novel bat-derived coronavirus, denoted RmYN02, identified from a metagenomics analysis of samples from 227 bats collected from Yunnan Province in China between May and October, 2019. RmYN02 shared 93.3% nucleotide identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 21 publications
(36 reference statements)
5
58
0
Order By: Relevance
“…Our study provides a structural context to the S1/S2 insert, which has also been reported by others [52,62]. The presence of a distinct insert containing paired basic residues in the S1/S2 priming loop is common in many coronaviruses in Betacoronavirus lineage C (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Our study provides a structural context to the S1/S2 insert, which has also been reported by others [52,62]. The presence of a distinct insert containing paired basic residues in the S1/S2 priming loop is common in many coronaviruses in Betacoronavirus lineage C (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…We demonstrate that the sarbecoviruses circulating in horseshoe bats have complex recombination histories 5 / 25 permitting generation of novel viral variants, as reported by others (He et al, 2014;Hon et al, 2008;Hu et al, 2017;Li et al, 2020b;Lin et al, 2017;Wang et al, 2017;Yuan et al, 2010;Zhou et al, 2020a).…”
Section: Introductionsupporting
confidence: 76%
“…When viewing the last 7kb of the genome a clade of viruses from northeast (NE) China appears to cluster with sequences from south-central (SC) Chinese provinces, but when inspecting trees from different parts of ORF1ab the NE China clade is phylogenetically separated from the SC China clade. Individual sequences such as RpShaanxi2011, Guangxi GX2013, and two sequences from Zhejiang province (CoVZXC21/CoVZC45), as previously shown Zhou et al, 2020a), show strong phylogenetic recombination signals, as they fall on different evolutionary lineages (with bootstrap support > 80%) depending what region of the genome is being examined.…”
Section: Recombination Analysis and Identification Of Breakpoint-freementioning
confidence: 69%
See 1 more Smart Citation
“…This PRRA motif makes the S1/S2 cleavage in SARS-CoV-2 much more efficiently than in SARS-CoV and may expand its tropism and/or enhance its transmissibility (23). A recent study of bat CoVs in Yunnan, China, identified a three-amino acid insertion (PAA) at the same site (26). Although it is not known if this PAA motif can function like the PRRA motif, the presence of a similar insertion at the same site indicates that such insertion may already be present in the wild bat CoVs.…”
Section: Acquisition Of Receptor Binding Motif Through Recombinationmentioning
confidence: 99%